2020
DOI: 10.1186/s40659-020-00285-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-185-5p response to usnic acid suppresses proliferation and regulating apoptosis in breast cancer cell by targeting Bcl2

Abstract: Background: Breast cancer is the most common cancer types among women. Recent researches have focused on determining the efficiency of alternative molecules and miRNAs in breast cancer treatment. The aim of this study was to determine the effect of usnic acid response-miR-185-5p on proliferation in the breast cancer cell and to determine its relationship with apoptosis pathway. Methods: The cell proliferation and cell apoptosis rate were significantly increased following the ectopic expression of miR-185-5p in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…MiR‐185‐5p has been reported to participate in the process of cell death in response to various cell stresses, including hypoxia/ischaemia injury. 27 , 28 , 44 A recent study indicated that inhibition of miR‐185‐5p in endothelial cells contributed to the recovery of heart function after MI. 29 However, the exact mechanism by which miR‐185‐5p regulates cardiomyocyte pyroptosis after hypoxia‐ischaemia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐185‐5p has been reported to participate in the process of cell death in response to various cell stresses, including hypoxia/ischaemia injury. 27 , 28 , 44 A recent study indicated that inhibition of miR‐185‐5p in endothelial cells contributed to the recovery of heart function after MI. 29 However, the exact mechanism by which miR‐185‐5p regulates cardiomyocyte pyroptosis after hypoxia‐ischaemia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 25 MiR‐185‐5p was reported to function as a tumour suppressor by inhibiting proliferation and inducing apoptosis in cancers. 26 , 27 , 28 Recently, one study has revealed that downregulation of miR‐185‐5p expression contributes to neovascularization in endothelial cells, which further mitigates the decline in cardiac function in postinfarction mice. 29 Previous studies have suggested that lncRNAs could bind to miRNAs and act as competitive endogenous RNAs (ceRNAs) to regulate cell biological processes, which play a vital role in myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…In BC, miRNA also has a significant regulatory effect. For example, miR-185-5p induces a higher level of apoptosis in BC cells by targeting Bcl-2 [ 33 ]. Additionally, miR-615-3p is upregulated in BC and enhances EMT and metastasis of BC by targeting the PICK1/TGFBRI axis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kılıç et al (2019) determined that 67 miRNAs are specifically responsive to usnic acid (lichen secondary metabolite) in MDA-MB-231 cells, while 15 and 8 are specific to BT-474 and MCF-7 cells, respectively [ 27 ]. Değerli et al (2020) identified miR-185-5p as the most promising usnic acid response of miRNAs in BT-474 breast cancer cells [ 39 ]. In this study, we determined that vulpinic acid responsive miRNAs.…”
Section: Discussionmentioning
confidence: 99%